Emerging third-sector sports organisations and navigating uncertainty in an 'era of austerity': a single ethnographic case study from Liverpool. Issue 1 (2nd January 2018) - Kenyon, James Andrew; Mason, Carolynne; Rookwood, Joel
ABSTRACT: There have been a number of recent policies in the UK which have attempted to capitalise on the benefits that sport potentially offers for health and well-being. These are, however, set against a somewhat incongruous backdrop of reductions in opportunities to participate, resulting from the ongoing constraints on public spending associated with austerity. In response to these constraints, an increasing number of third-sector sports organisations (TSSOs) have emerged to fill some of the gaps left by the public services that local authorities are no longer able deliver. This research draws on the experiences of one of those TSSOs, Target Football, a Community Interest Company located in Princes Park, Liverpool, one of the most deprived neighbourhoods in the UK. Drawing upon 6 years of ethnographic research, and a posteriori semi-structured interviews, this paper examines the ways in which this TSSO has navigated – and continues to navigate – the contextual uncertainty arising from austerity, to sustain sports provision in an environment where opportunities have declined in recent years. Underpinned by stakeholder theory, this research examines the relationships that exist between organisations and their stakeholders, and frames these in relation to power, legitimacy and urgency. The findings provide insight into the significant obstacles that challenge the survival of TSSOs in the context of a scarcity of resources. From a more practical perspective, these findings also provide critical insight into David Cameron's aspiration 'to do more with less'.